LOCAL VALUES AND WISDOM OF THE EARTH ALMS TRADITION IN PULAU PANGGUNG VILLAGE, MUSI RAWAS REGENCY: Nilai Dan Kearifan Lokal Tradisi Sedekah Bumi Desa Pulau Panggung Kabupaten Musi Rawas - Reva Anggini; Yoga Alvin Almada; Bella Agustina; Yadri Irwansyah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The sedekah bumi tradition is a form of local wisdom that continues to be preserved by rural communities as an expression of gratitude for agricultural yields and as a means of strengthening social relationships. This study aims to describe the values and local wisdom embedded in the sedekah bumi tradition in Pulau Panggung Village, Musi Rawas Regency. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research informants consisted of traditional leaders, community leaders, and local residents who were directly involved in the implementation of the sedekah bumi tradition. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that the sedekah bumi tradition contains religious, social, mutual cooperation, togetherness, and environmental care values. In addition, this tradition functions as a medium for transmitting cultural values to the younger generation in order to preserve local identity and wisdom. Therefore, the sedekah bumi tradition not only holds ritual significance but also plays an important role in maintaining social harmony and preserving local culture in Pulau Panggung Village.